PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN TIKET MASKAPAI AIRASIA - Viamrina Dewi, Ivana; Mahadewi, NPE.; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024)DO - 10.24843/IPTA.2024.v12.i01.p10, 2024)
This research aims to explain the influence of the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) on the purchase decisions of flight tickets on AirAsia Indonesia. The questionnaires were distributed to 105 respondents through online platforms, and interviews were also conducted with several AirAsia users using a nn- probability sampling. The data analysis method used multiple linear regression analysis using IBM SPSS Statistics 26 for Windows. The results of the research indicate that, partially, the variables of product, price, process, people, and physical evidence have a positive and significant influence on the purchase decisions of flight tickets on AirAsia Indonesia. Meanwhile, the variables of promotion and place do not have a significant influence on purchase decisions. Simultaneously, all elements of the marketing mix, consisting of product, price, promotion, place, process, people, and physical evidence, collectively have a positive and significant influence on the purchase decisions. The R-squared value obtained in this research is 0.706, which means that 70.6% of the purchase decisions are influenced by marketing mix strategies, while the remainder is affected by other factors not covered in this study.